PENERAPAN STRATEGI FORMASI REGU TEMBAK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 5 PEKANBARU - Yestrik, Ismalia Yestrik Ismalia; Copriady, Jimmi Copriady Jimmi; ', Rasmiwetti Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student achievement on the subject ofhydrocarbons in the first year student of SMAN 5 Pekanbaru by application of a firingsquad formation strategy. Form of research is experimental with pretest-posttest design.The sample consists of two classes, class X.2 as an experimental class and class X.6 asthe control class is determined randomly after normality test and homogeneity test.Experimental class were treated by application of a firing squad formation strategywhile grade control without firing squad formation strategy implementation. Dataanalysis technique used was t-test. Based on the final results of data processing using ttestformula obtainable tarithmetic>ttable is 4,99> 1,67 meaning that the application of afiring squad formation strategies can improve student achievement on the subject ofhydrocarbons in the first year student of SMAN 5 Pekanbaru. The raising studentachievement category in the experimental class including normalized gain a high scoreof 0.82.Keywords: Strategy formation firing squad, learning achievement